Poezja jako tożsamość osobowa u Czesława Miłosza - Bieńkowska, Ewa (Colloquia Litteraria, 2011)
The author brings up the problem connected with the intersection (coherence) of „personal rightness” and „poetic rightness” in Czesław Miłosz’s literary output; she endeavours to interpret his poetry as a distinct mark of personal identity. In odrer to do so she refers to such crucial contexts of Miłosz’s writing, the authos of „Ziemia Urlo” as, for instance, Polish romanticism and French writers. The sketch becomes concluded by the necessary – for the poet himself – acceptance by the others.